The Effect of M-Banking Use and Transaction Security on Customer Investment Decisions with Financial Behavior as an Intervening Variable at BNI Bank in Bukittinggi City - Suci Nofita Sari; Lusiana Lusiana; Fitri Yeni (Sean Institute, 2026)
This study aims to examine the influence of mobile banking usage and transaction security on customer investment decisions, with financial behavior as an intervening variable at Bank BNI in Bukittinggi City. Data collection was conducted through a survey and questionnaire distribution, with a sample of 100 respondents. The analysis method used was structural equation modeling using SmartPLS. The results showed a significant influence of mobile banking on financial behavior. Transaction security significantly impacted financial behavior. M-banking significantly impacted investment decisions. Transaction security significantly impacted investment decisions. Financial behavior significantly impacted investment decisions. Financial behavior mediated the influence of mobile banking on investment decisions. Financial behavior mediated the influence of transaction security on investment decisions.